The impact of delayed access to COVID-19 vaccines in low- and lower-middle-income countries - Duroseau, Brenice; Kipshidze, Nodar; Limaye, Rupali Jayant (Frontiers in Public Health, 2023)
A majority of low income (LIC) and lower-middle-income countries (LMIC) were unable to achieve at least 10% population coverage during initial vaccine rollouts, despite the rapid development of the Coronavirus disease 2019 (COVID-19) vaccines. Nearly three years into this pandemic, evaluating the impact of inequities in vaccine access, uptake, and availability is long overdue. We hypothesized that a delay in receiving COVID-19 vaccines was associated with an increased toll on cumulative cases and mortality. Furthermore, this relationship was modified by the size of a country’s economy. We performed an ecological study assessing these relationships, in which a country’s economic standing was assessed by World Bank Income Classification, gross domestic product based on purchasing power parity (GDP PPP) per Capita category, and crude GDP PPP. Countries with the smallest economies reported first vaccination much later than larger economies on all three rankings, as much as 100 days longer. Among low-income countries, a one-day increase until first vaccination was associated with a 1.92% (95% CI: 0.100, 3.87) increase in cumulative cases when compared to high-income countries (p = 0.0395), when adjusting for population size, median age, and testing data availability. Similarly, among the lowest GDP PPP countries a one-day increase until first vaccination was associated with a 2.73% (95% CI: 0.100, 5.44) increase in cumulative cases when compared to the highest GDP PPP countries (p = 0.0415). When modeling cumulative mortality, effects in the same direction and magnitude were observed, albeit statistically non-significant. Economic standing modified the effects of delayed access to COVID-19 vaccination on cumulative cases and mortality, in which LMICs tended to fare worse than high-income countries despite the rollout of vaccines. These findings highlight the importance of prioritizing equitable and timely access to COVID-19 vaccines across all countries, irrespective of economic size. Future studies should examine the impacts that vaccine inequities had on local transmission dynamics.